Nacre-inspired polymer composites with high thermal conductivity and enhanced mechanical strength. (June 2019) - Zhang, Tao; Sun, Jiajia; Ren, Linlin; Yao, Yimin; Wang, Mingmei; Zeng, Xiaoliang; Sun, Rong; Xu, Jian-Bin; Wong, Ching-Ping
Abstract: Polymer composites with high thermal conductivity are attracting increasing interest as thermal-management materials owing to material abundance, easy processing and low cost. However, conventional preparation of thermally conductive polymer composites through adding high-loading inorganic fillers usually suffers from poor mechanical properties. Here, inspired by the microstructure of natural nacre, we report on fine ordered Ag-BN/epoxy resin composites via interfacial manipulation of boron nitrides with Ag nanoparticles and hot-pressing induced orientation process. The as-prepared nacre-like compounds have both high thermal conductivity (up to 23.1 W m −1 K −1 ) and mechanical strength (tensile strength of 80.3 MPa). This work provides a novel insight into the fabrication of polymer composites with superior mechanical strength in thermal management field.